Aromatic components and endophytic fungi during the formation of agarwood in Aquilaria sinensis were induced by exogenous substances - Pang, Shengjiang; Zhao, Weiwei; Zhang, Qingqing; Tian, Zuwei; Wu, Dan; Deng, Shuokun; Zhang, Pei; Li, Zhongguo; Liu, Shiling; Yang, Baoguo; Huang, Guihua; Zhou, Zaizhi (Frontiers in Microbiology, 2024)
The process of formation of aromatic components for agarwood in Aquilaria sinensis is closely related to endophytic fungi and the result of complex multiple long-term joint interactions with them.However, the interactions between the aromatic components and endophytic fungi remain unclear during the formation of agarwood. In this study, precise mixed solution of hormones, inorganic salts, and fungi was used to induce its formation in A. sinensis, and sample blocks of wood were collected at different times after inoculation. This study showed that the aromatic compounds found in the three treatments of A. sinensis were primarily chromones (31.70%-33.65%), terpenes (16.68%-27.10%), alkanes (15.99%-23.83%), and aromatics (3.13%-5.07%). Chromones and terpenes were the primary components that characterized the aroma. The different sampling times had a more pronounced impact on the richness and diversity of endophytic fungal communities in the A. sinensis xylem than the induction treatments. The species annotation of the operational taxonomic units (OTUs) demonstrated that the endophytic fungi were primarily composed of 18 dominant families and 20 dominant genera. A linear regression analysis of the network topology properties with induction time showed that the interactions among the fungal species continued to strengthen, and the network structure tended to become more complex. The terpenes significantly negatively correlated with the Pielou evenness index (P< 0.05), while the chromones significantly positively correlated with the OTUs and Shannon indices.